Influence of microstructural defects and the surface topography on the fatigue behavior of "additively‐subtractively" manufactured specimens made of AISI 316L. Issue 5 (14th May 2021) - Blinn, B.; Greco, S.; Smaga, M.; Zimmermann, M.; Hotz, H.; Müller, D.; Hartig, J.; Kirsch, B.; Aurich, J.C.; Beck, T.
Abstract: As additive manufacturing offers only low surface quality, a subsequent machining of functional and highly loaded areas is required. Thus, a sound knowledge of the interrelation between the additive and subtractive manufacturing process as well as the resulting mechanical properties is indispensable. In this work, specimens were manufactured by using laser‐based powder bed fusion (L‐PBF) with substantially different sets of process parameters as well as subsequent grinding (G) or milling (M). Despite the substantially different surface topographies, the fatigue tests revealed only a slight influence of the subtractive manufacturing on the fatigue behavior, whereas the different laser‐based powder bed fusion process parameters led to pronounced changes in fatigue strength. In contrast, a significant influence of subtractive finishing on the fatigue properties of the defect‐free continuously cast (CC) reference specimens was observed. This can be explained by a dominating influence of process‐induced defects in laser‐based powder bed fusion material, which overruled the influence of surface machining. However, although both laser‐based powder bed fusion parameter sets resulted in substantial defects, one set yielded similar fatigue strength compared to continuously cast specimens. Abstract : In this work, the influence of process parameters used in laser‐based powder bed fusion and subsequent machining (grinding, milling) on the fatigue behavior was analyzed. Besides a differently pronounced interrelation of microstructure and machining between additively and conventionally manufactured material, the results show a high impact of process‐induced defects on lifetime, and on the effects of machining on fatigue behavior. Translation abstract: Da die additive Fertigung zu einer geringen Oberflächengüte führt, ist eine spanende Nachbearbeitung von hochbeanspruchten Bereichen oder Funktionsflächen notwendig, weshalb ein Verständnis der Wechselwirkung zwischen additiver und subtraktiver Fertigung und den hieraus resultierenden mechanischen Eigenschaften unabdingbar ist. In dieser Arbeit wurden Proben mittels laserbasiertem Pulverbettschmelzen (L‐PBF), unter Verwendung zweier substantiell unterschiedlicher Parametersätze, sowie nachgelagertem Schleifen (G) bzw. Fräsen (M) hergestellt. Trotz der unterschiedlichen Oberflächentopographien zeigten die Ermüdungsversuche nur einen geringen Einfluss der Nachbearbeitung auf die Ermüdungslebensdauer, während die verschiedenen, im laserbasierten Pulverbettschmelzen verwendeten Prozessparameter zu deutlich anderen Ermüdungsfestigkeiten führten. Für die stranggegossenen, defektfreien Referenzproben (CC) wurden hingegen erhebliche Auswirkungen der Nachbearbeitung auf das Ermüdungsverhalten beobachtet. Dies kann auf den dominierenden Einfluss prozessinduzierter Defekte bei den mittels laserbasierten Pulverbettschmelzen hergestellten Proben zurückgeführt werden. Trotz der Defekte war jedoch für einen dieser Zustände eine zu den stranggegossenen, defektfreien Referenzproben vergleichbare Ermüdungsfestigkeit festzustellen.